The Play of Political Culture, Emotion and Identity - Yates, Candida. author. aut Link
VII, 194 p. 1 illus.
Keywords: Offering a uniquely 'psycho-cultural' take on the emotional dynamics of UK political culture this book uses theories and research in psychoanalysis, cultural and media studies and political sociology. It explores the cultural and emotional processes that shape our relationship to politics in a media age, referencing Joanna Lumley to Nigel Farage.